집단 미술치료 프로그램이 통합교육을 받는 정신지체 유아들의 사회성에 미치는 효과 - 박동찬 (The Graduate School, Ajou University, 2006)
The purpose of this research is to verify the effectiveness of the group art therapy on the sociality-improvement of the mentally retarded children and the acceptance-improvement of the normal children for the mentally handicapped. The research has been done to prove it by observing three mentally retarded children and six normal children who have the united education in one class together, which was done for forty minutes a day, two times a week, from April 19th to August 22nd in 2005, totally 31 times. The conclusion of this research through the comparative analysis from this paper result is as follows. First, the group art therapy in unified class has resulted in positive effect on sociality-improvement of the mentally retarded children. That is, mentally-retarded children have improved their ability to express themselves, relationships between others and cooperationships through group art therapy. Second, the group art therapy in unified class has shown a positive effect on the acceptance-improvement of the normal children for the handicapped children In short, the program of the group art therapy in unified class led natural contacts between the handicapped and the normal, so there could be the media of the accepting each other. Two sides of the children also enjoyed the interaction with the same aged children and became to know how to express their own emotion. By experiencing the share and the common of the drawing materials, they recognized and respected friends of that age. As this paper shows, group art therapy helps the mentally retarded children express their inner feelings and make the linguistic expression easier. It also relieves the tension and anxiety in them, and it can help the retarded show theirselves naturally, controlling their conflict. At the same time, through the self-expression and the sublimation, the mentally retarded children can encourage their own self-growth. The existing research until now have been biased on one side and showed only the therapy-effect, however, by doing the unified education of the two groups of children in a class, the sociality-improvement of the mentally retarded children and the acceptance-improvement of the normal children for the retarded were proved. The meaning of this research is that the two effects were studied at the same time.
학위논문(석사)--아주대학교 교육대학원 :특수교육,2006. 2